Leptospira spp. and Toxoplasma gondii antibodies in vampire bats (Desmodus rotundus) in Botucatu region, SP, Brazil - Zetun, C. B. [UNESP]; Hoffmann, J. L. [UNESP]; Silva, R. C. [UNESP]; Souza, L. C. [UNESP]; Langoni, Helio [UNESP] (FapUNIFESP (SciELO), 2009)
The destruction of natural ecosystems has caused several problems to humans and other animals; herein we investigate the close relationship among vampire bats, humans and domestic animals. Toxoplasma gondii and Leptospira spp. infections are two worldwide zoonoses that provoke serious damage to animals. To determine the prevalence of bats seropositive for toxoplasmosis and leptospirosis in the Botucatu region, 204 serum samples of vampire bats (Desmodus rotundus) were tested for T. gondii antibodies by modified agglutination test (MAT-t) and for Leptospira spp. by microscopic agglutination test (MAT-l). No animal was tested positive for T. gondii while leptospiral positivity was 7.8% for Pyrogenes, Shermani and Javanica serovars, with titers varying from 100 to 1,600. Thus, it was verified that D. rotundus does not play a relevant role in toxoplasmosis epidemiology. However, these bats can be important in the maintenance of Leptospira spp. in the environment.
Keywords: Public health; Serological survey; Vampire bats; Zoonosis